1985
DOI: 10.1002/ijch.198500122
|View full text |Cite
|
Sign up to set email alerts
|

Extensions of the Melander–Westheimer Postulate: Isotope Effects in Reactions with Equilibrium Values Far from Unity

Abstract: The symmetric dependence of experimental primary kinetic isotope effects on the free energy change, obtained for reaction series with zero equilibrium isotope effects, can be inverted to obtain the free energy profile along the reaction coordinate. Trends in the kinetic isotope effects for the general case of non‐vanishing equilibrium effects can be understood by an extension of the same theory. Comparison is made with experiments for reactions of halogen atoms with hydrogen/deuterium molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Many years ago Melaner and Westheimer have suggested that, within a reaction series, the KIE should exhibit a symmetric maximum when Δ G = 0. Such behavior can be obtained from the structure−reactivity correlations, e.g., eqs 4.1, if only Δ varies with isotopic substitution. The correlation may be nonsymmetric if also Δ G is isotopically dependent, as observed for the H 2 + X series (X a halogen atom) . In this case the KIE decreases faster for negative Δ G values.…”
Section: The Dissociation Eventmentioning
confidence: 99%
See 1 more Smart Citation
“…Many years ago Melaner and Westheimer have suggested that, within a reaction series, the KIE should exhibit a symmetric maximum when Δ G = 0. Such behavior can be obtained from the structure−reactivity correlations, e.g., eqs 4.1, if only Δ varies with isotopic substitution. The correlation may be nonsymmetric if also Δ G is isotopically dependent, as observed for the H 2 + X series (X a halogen atom) . In this case the KIE decreases faster for negative Δ G values.…”
Section: The Dissociation Eventmentioning
confidence: 99%
“…[58][59][60] The correlation may be nonsymmetric if also ∆G is isotopically dependent, as observed for the H 2 + X series (X a halogen atom). 96 In this case the KIE decreases faster for negative ∆G values. Interestingly, the same asymmetry is observed for ESPT to water in Figure 12, although the data here are less accurate so it is difficult to say what is the origin of its asymmetry.…”
mentioning
confidence: 92%